Contribution of genotypes in Prothrombin and Factor V Leiden to COVID-19 and disease severity in patients at high risk for hereditary thrombophilia - GEÇKİNLİ, BİLGEN BİLGE; ALAVANDA, CEREN (My University, 2023)
Thrombotic and microangiopathic effects have been reported in COVID-19 patients. This study examined the contribution of the hereditary thrombophilia factors Prothrombin (FII) and Factor V Leiden (FVL) genotypes to the severity of COVID-19 disease and the development of thrombosis. This study investigated FII and FVL alleles in a cohort of 9508 patients (2606 male and 6902 female) with thrombophilia. It was observed that 930 of these patients had been infected by SARS-CoV-2 causing COVID-19. The demographic characteristics of the patients and their COVID-19 medical history were recorded. Detailed clinical manifestations were analyzed in a group of cases (n = 4092). This subgroup was age and gender-matched. FII and FVL frequency data of healthy populations without thrombophilia risk were obtained from Bursa Uludag University Medical Genetic Department\"s Exome Databank. The ratio of males (31.08%; 27.01%) and the mean age (36.85 ± 15.20; 33.89 ± 14.14) were higher among COVID-19 patients compared to non-COVID-19 patients. The prevalence of FVL and computerized tomography (CT) positivity in COVID-19 patients was statistically significant in the thrombotic subgroup (p < 0.05). FVL prevalence, CT positivity rate, history of thrombosis, and pulmonary thromboembolism complication were found to be higher in deceased COVID-19 patients (p < 0.05). Disease severity was mainly affected by FVL and not related to genotypes at the Prothrombin mutations. Overall, disease severity and development of thrombosis in COVID-19 are mainly affected by the variation within the FVL gene. Possible FVL mutation should be investigated in COVID-19 patients and appropriate treatment should be started earlier in FVL-positive patients.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Viroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Virology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; VİROLOJİ; BULAŞICI HASTALIKLAR; Life Sciences (LIFE); IMMUNOLOGY; VIROLOGY; INFECTIOUS DISEASES; Bulaşıcı hastalıklar; Infectious Diseases; COVID-19; Factor V Leiden; Prothrombin; thrombophilia; cOVID‐19; Factor V Leiden; Prothrombin; thrombophilia